Fabrication of hierarchical TiO2 coated Co20Ni80 particles with tunable core sizes as high-performance wide-band microwave absorbers. Issue 38 (16th September 2016) - Chen, Chen; Liu, Qinghe; Bi, Han; You, Wenbin; She, Wen; Che, Renchao
Abstract : Multifunctional composite microspheres with a Co20 Ni80 core and anatase TiO2 shells (Co20 Ni80 @TiO2 ) are synthesized by combining a solvothermal reaction and a calcination process, and include a series of microspheres with different core sizes (100 nm, 500 nm and 1 μm). Abstract : Multifunctional composite microspheres with a Co20 Ni80 core and anatase TiO2 shells (Co20 Ni80 @TiO2 ) are synthesized by combining a solvothermal reaction and a calcination process, and include a series of microspheres with different core sizes (100 nm, 500 nm and 1 μm). The mechanism of self-assembly of the primary particles has been effective in both the fabrication of the core and the process of coating. The obtained core–shell particles possess superior monodispersity, size uniformity, and tailored core sizes, and are characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Furthermore, the electromagnetic shielding performance of the microspheres is investigated in terms of the theory of transmission lines. The Co20 Ni80 @TiO2 core–shell particle (CoNi@TiO2 ) with a well-defined core size of 500 nm demonstrates a remarkable wide-band electromagnetic shielding performance of up to 6.2 GHz (10.0–16.2 GHz, <−10 dB) within 2–18 GHz, which is due to the tunable multi-component hierarchical structure of the particles and contributes to the complex permittivity and permeability and the multiple scattering loss of the microwave. The Co20 Ni80 @TiO2 particle with a specific core size (500 nm) is a promising candidate for the wide-band electromagnetic shielding materials, gathering increasing interest from researchers.